Analysis Of The Settlement Of Criminal Offenders Who Possess Drugs Without A License Through Restorative Justice Based On Police Regulation Number 8 Of 2021 Concerning Handling Criminal Acts Based On Restorative Justice - Muhammad Hatta Roma Tampubolon; Andi Bustamin Dg. Kunu; Hanifah dhiyanul Haq (JURNAL HUKUM SEHASEN, 2023)
The Regulation of the National Police of the Republic of Indonesia or often called the National Police Regulation or Perpol on Handling Crimes based on Restorative Justice is a step taken by the National Police in realizing the resolution of criminal acts by prioritizing Restorative Justice which emphasizes restoring back to its original state and balancing the protection and interests of victims and perpetrators of criminal acts that are not oriented towards punishment is a legal necessity in society. The problems in this study are What are the factors that cause the perpetrator to own drugs without a license? How is the process of resolving criminal acts that own drugs without a license through Restorative Justice against criminal offenders who own drugs without a license (Case Study of Police Regulation Number 8 of 2021 concerning Handling Crimes Based on Restorative Justice)? The research methods used are normative juridical approaches and empirical approaches, the data used are secondary data and primary data with qualitative analysis in order to obtain a correct and objective research result.The results of the study are the factors that cause the perpetrator to commit a criminal act of possessing drugs without a license (Case Study of Police Regulation Number 8 of 2021 concerning Handling Crimes Based on Restorative Justice), namely the intention of the perpetrator, Factors of low education, and factors of low morale and religious knowledge, the process of resolving crimes that possess drugs without a license through restorative justice against criminal offenders who possess drugs without a license (Case Study of Police Regulation Number 8 of 2021 concerning Handling Crimes Based on Restorative Justice), namely criminal offenders who possess drugs without a license are carried out as long as they can be categorized as addicts, abusers, victims of abuse, narcotics dependence, & one-day narcotics use as regulated in the Joint Regulation of the Chief Justice of the Supreme Court, Minister of Law and Human Rights, Minister of Health, Minister of Social Affairs, Attorney General, Chief of Police, Head of the National Narcotics Agency Number 01/PB/MA/111/2014, Number 03 of 2014, Number 11 of 2014, Number 03 of 2014, Number Per005/A/JA/03/2014, Number 1 of 2014, Number Perber/01/111/2014/BNN on Handling Narcotics Addicts and Victims of Narcotics Abuse into Rehabilitation Institutions. Restorative Justice can also be applied if it meets the conditions, namely when caught red-handed by Police investigators and / or investigators of the National Narcotics Agency (BNN), evidence of one-day use is found and also has assessment results from the Integrated Assessment Team at each submission of case files, The author's suggestion is that the police, prosecutors, and judiciary should be more careful in providing recommendations for medical rehabilitation to drug abusers.